Percutaneous endoscopic gastrostomy can improve survival outcomes in patients with N3 nasopharyngeal carcinoma undergoing concurrent chemoradiotherapy. (October 2021) - Xu, Yun; Chen, Mengwei; Guo, Qiaojuan; Peng, Hewei; Guo, Lanyan; Zong, Jingfeng; Huang, He; Chen, Bijuan; Xu, Hanchuan; Pan, Jianji; Lin, Shaojun
Highlights: PEG may maintain the nutritional status and improve treatment compliance. N3 NPC patients who underwent PEG had significantly higher 5-year OS and PFS. PEG was an independent factor for N3 survival. PEG can maintain the nutritional status and improve the treatment completion rate. Abstract: Objectives: Our previous study revealed that percutaneous endoscopic gastrostomy (PEG) and intensive nutritional support may minimize body weight loss, maintain nutritional status, and offer better treatment tolerance for patients with locally advanced nasopharyngeal carcinoma (LA-NPC) during concurrent chemoradiotherapy (CCRT). This study aimed to further explore the potential long-term survival benefits of PEG in LA-NPC. Methods: Between June 1, 2010 and June 30, 2014, a total of 133 consecutive LA-NPC patients who received prophylactic PEG (pPEG) feeding before the initiation of CCRT were included. Meanwhile, an additional 133 non-PEG patients, who were matched for age; sex; and tumor, node, and metastases stage, were selected as control cohort. The log-rank test was used to compare survival distributions between groups. Multivariate prognosis analysis was conducted using a Cox's proportional hazards regression model. Results: After a median follow-up time of 81 months (range: 4–119 months), pPEG was not associated with significant survival benefits in the whole cohort. However, the N3 NPC patients who underwent PEG had significantly higher 5-year overall survival (OS) and progression-free survival (PFS) (84.0 and 76.0%, respectively) than those who did not undergo PEG (56.7 and 45.6%, respectively; p  < 0.05). Univariate and multivariate analyses demonstrated that PEG was an independent factor for N3 survival. Conclusion: PEG can maintain the nutritional status and improve the rate of treatment completion for LA-NPC patients who underwent CCRT, and these advantages can transfer into survival benefits in N3 NPC. Further multicenter prospective clinical trials are warranted.